Application of HBV Model in Hydrological Studies of Nepali River Basins: A Case Study - Shrestha, Subarna; Alfredsen, Knut (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Ungauged basins are challenges for hydrological study, the key discipline to analyse for planning and the operation of water resources projects. Several river basins have no hydrologic measurements where there is feasibility of promising water resources schemes. This study deals with use of the Hydrologiska Byråns avdeling for Vattenbalans (HBV) hydrological model to generate stream flow time series and other hydrological variables. The model was calibrated successfully in the Sanghutar catchment of the Likhu River of Nepal, and then used to simulate runoff series at the proposed intake site of Likhu HEP, where the gauging station has not been installed. The model can be used to generate runoff of other ungauged catchments which have similar catchment characteristics. DOI: http://dx.doi.org/10.3126/hn.v8i0.4910 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page: 38-43 Uploaded date: 17 June, 2011